2021
DOI: 10.1111/bjh.17733
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and survival in 16 098 patients with non‐Hodgkin lymphoma or chronic lymphocytic leukaemia treated in the rituximab era

Abstract: Summary Statin use has been associated with reduced mortality from several cancers but also suggested, in vitro, to diminish the effectiveness of lymphoma treatments including rituximab. The present study aimed to assess the association of statin use with mortality in patients with non‐Hodgkin lymphoma (NHL) and chronic lymphocytic leukaemia (CLL). We identified all incident NHLs and CLLs in Sweden from 2007 to 2013 with subtype information in the Swedish Lymphoma and Cancer Registers. Using Cox regression, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…In the final step of full-text review, another 20 studies were excluded according to the reasons listed in Figure 1. Finally, eight cohort studies were identified and included in the meta-analysis [13][14][15][16][17][18][19][20].…”
Section: Identification Of Related Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In the final step of full-text review, another 20 studies were excluded according to the reasons listed in Figure 1. Finally, eight cohort studies were identified and included in the meta-analysis [13][14][15][16][17][18][19][20].…”
Section: Identification Of Related Studiesmentioning
confidence: 99%
“…Eight cohort studies [13][14][15][16][17][18][19][20] involving 9927 patients with DLBCL contributed to this meta-analysis.…”
Section: Summary Of Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Так, в про веденном в 2021 г. исследовании с участием 16 098 боль ных неходжкинскими лимфомами и ХЛЛ, из которых 20 % принимали статины на момент постановки ди агноза, не показано влияния данных препаратов на смертность, связанную с заболеванием. Однако досто верно установлена ассоциация приема статинов с мень шей летальностью от всех причин и сердечнососудистых осложнений, что свидетельствовало о целесообраз ности приема этих препаратов [16]. Данное обстоя тельство позволяет предположить возможность исполь зования статинов не только у взрослых, но и у детей с гемобластозами, поскольку выявлена ассоциация развития атеросклероза с ОЛЛ [3], ОМЛ [5] и хрони ческим миеломоноцитарным лейкозом [6].…”
Section: клинические исследования роли статинов в сопроводительном ле...unclassified